Online fundraising, self-image, and the long-term impact of ask avoidance - Maja Adena; Steffen Huck (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We study an online fundraising campaign run on an opera ticket booking platform. After establishing a baseline, a first change doubled the donation grid. A second change altered the navigation of the website rendering the act of declining to donate more salient. The contribution of our paper is fourfold. First, we add to the literature on defaults by showing how donation grids can have dramatic impacts on giving. Second, we demonstrate that small, apparently superficial changes in the design of a campaign can have unexpectedly large consequences (offsetting the effects of changes in the choice architecture). Third, we provide the first field evidence for the role of self-image in charitable giving. Finally, we provide stark evidence on possible adverse long-run effects of fundraising campaigns for ticket selling entities. “Avoiding the ask,” non-frequent customers buy fewer tickets in the following opera season. Ticket sales per person fall by exteuro35, while average charitable income from the same group during the campaign had been just under exteuro0.12.
Keywords: D64; D03; D12; 330